AgOTf‐Catalyzed Tandem Reaction of Oxabenzonorbornadienes with Arylacetylenes. Issue 10 (12th August 2015) - Zhou, Yongyun; Liu, Shanshan; Chen, Hualei; Chen, Jingchao; Sun, Weiqing; Li, Sifeng; Yang, Qingjing; Fan, Baomin
Abstract A tandem isomerization/hydroarylation reaction of oxabenzonorbornadienes and arylacetylenes was realized by using AgOTf as catalyst. 1, 1‐Diarylethylenes could be easily generated as products in moderate to good yields in this tandem reaction.